Le Devin historien en Mésopotamie - Glassner, Jean-Jacques. (Ancient Magic and Divination, 2019)
Le devin historien en Mesopotamie is a combined study of divination and historiography. More than mere custodians of historical memory, diviners approached omens as written signs and developed a sophisticated semiology to recognize and order them. Diviners perceived omens as potentially rich in various meanings and cultivated an elaborate hermeneutic for working these out using hypothetical and inductive reasoning. Even if omens were removed from the recorded facts, diviners endowed them with a wide range of possibilities. Divination sought to establish links among historical, cosmic, and natural events because it investigated at once the past, present, and future. The first study of its kind since 1946, when only about 60 historical omens were known, this work presents 385 in a comprehensive edition.